Effects of Adverse Early‐Life Events on Aggression and Anti‐Social Behaviours in Animals and Humans. (October 2014) - Haller, J.; Harold, G.; Sandi, C.; Neumann, I. D.
<x xml:space="preserve">Abstract</x> We review the impact of early adversities on the development of violence and antisocial behaviour in humans, and present three aetiological animal models of escalated rodent aggression, each disentangling the consequences of one particular adverse early‐life factor. A review of the human data, as well as those obtained with the animal models of repeated maternal separation, post‐weaning social isolation and peripubertal stress, clearly shows that adverse developmental conditions strongly affect aggressive behaviour displayed in adulthood, the emotional responses to social challenges and the neuronal mechanisms activated by conflict. Although similarities between models are evident, important differences were also noted, demonstrating that the behavioural, emotional and neuronal consequences of early adversities are to a large extent dependent on aetiological factors. These findings support recent theories on human aggression, which suggest that particular developmental trajectories lead to specific forms of aggressive behaviour and brain dysfunctions. However, dissecting the roles of particular aetiological factors in humans is difficult because these occur in various combinations; in addition, the neuroscientific tools employed in humans still lack the depth of analysis of those used in animal research. We suggest that the analytical approach of the rodent models presented here may be successfully used to complement human findings and to develop integrative models of the complex relationship between early adversity, brain development and aggressive behaviour.